Ayurvedic Management of Schizophrenia: A Case Report (AYUSHDHARA, 2023)
Schizophrenia is unarguably one of the most devastating mental illnesses, that affect how a person thinks, feels and behaves. This leads to symptoms such as hallucinations, delusions, disorganized behavior and impaired cognitive ability. The life time prevalence of schizophrenia is about 0.7% and requires lifelong management like medications, psychotherapy, and adequate social support. Symptoms of Schizophrenia are similar to that of Unmada mentioned in Ayurveda classics. Ayurveda has proven promising results in reducing the symptoms and improving the quality of life.This paper deals with a diagnosed case of schizophrenia which can be correlated with Vatika Unmada with Kapha Anubandha based on signs and symptoms. A 38-year-old female patient approached in our OPD and took two courses of treatment in 2021 December and 2022 October with complaints of disturbed sleep, hearing voices, night mares, lack of confidence, inability to make decisions, fear and wandering. The treatment was planned based on the signs and symptoms. Snehapana, Virechana, Vasti and Nasya were done. The symptoms were assessed using Positive and Negative Syndrome Scale (PANSS). After the treatment the patient had considerable relief in the symptoms.